2002
DOI: 10.1080/02791072.2002.10399980
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Benzodiazepine Use Among Houston Arrestees

Abstract: While marijuana and cocaine are the two most prevalent drugs among arrestees, benzodiazepine use has surpassed that of opiates in several jurisdictions across the United States. Despite this proliferation, few scholarly works have focused on benzodiazepine use among individuals under criminal justice supervision. In the present study, the authors used Chi-square statistics and logistic regression to identify significant associations between recent benzodiazepine use (as measured by urinalysis), demographic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
1
Order By: Relevance
“…The mean age of the alprazolam-positive decedent was 36.3 years. In contrast to previous studies, which have found that benzodiazepine users were more likely to be black, 23 all 178 decedents in our series were white.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The mean age of the alprazolam-positive decedent was 36.3 years. In contrast to previous studies, which have found that benzodiazepine users were more likely to be black, 23 all 178 decedents in our series were white.…”
Section: Discussioncontrasting
confidence: 84%
“…22 An increase in benzodiazepine use has been reported in recent years. 23 We have studied 178 cases in which alprazolam was detected in postmortem toxicologic studies. We have also seen an increase in alprazolam-positive deaths over the last 3 years, with 45 cases found in 2001, 83 in 2002, and 50 in the first 8 months of 2003.…”
Section: Discussionmentioning
confidence: 99%
“…We included studies reporting diagnoses of substance abuse and dependence within the last year and who sampled prisoners within 3 months of arrival into prison. We also included only those studies with diagnoses made by clinical examination or by interviews using validated diagnostic instruments; surveys using self‐report measures only [13–15] or biological markers only (e.g. hair analysis) were ineligible [16,17].…”
Section: Methodsmentioning
confidence: 99%
“…There were a number of other reasons for exclusion: (1) failure to include the whole prison population or a random sample of this population [34–36]; (2) reporting of retrospective substance use while in prison in post‐release prisoners [37,38]; (3) reporting estimates from only prisoners selected for assessment or treatment of substance dependence [39,40]; (4) reporting of combined results for men and women [10]; (5) reporting of combined estimates for alcohol and drug misuse [41,42]; (6) greater than 50% non‐participation [43]; (7) measuring solely injectable substance use [36,39,44]; and (8) lack of standardized criteria or unclear definitions regarding either substance abuse or dependence [35,45–65]. A group of studies examining the prevalence of drug dependence as part of the Arrestee Drug Abuse Monitoring programme in the United States was excluded for this latter reason [13,14]; (9) one 1985 study that used diagnostic criteria according to the International Classification of Diseases, version 8 [66]. Sensitivity analyses demonstrated large heterogeneity between this and the others (e.g.…”
Section: Methodsmentioning
confidence: 99%